PENGEMBANGAN BUKU PENGAYAAN PENGETAHUAN â€œKAJIAN FISIS BATUBARAâ€ UNTUK SISWA SMA - Lubis, Mia Andina; Desnita, Desnita; Permana, A. Handjoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study was conducted to develop the standardized knowledge-enrichment book for Senior High School Students. This book was tended to the students who have completely mastered the Physics materials in comprehending the limitation of energy sources and its effect for humanâ€™s life, as stated in the Main Competency (Kompetensi Dasar) of the existing Curriculum. The research method used is Research and Development which refers to ADDIE Development Model (Analysis, Design, Development, Implementation, and Evaluation). Questionnare was given as the assessment-instrument of the study which consists of four indicators; material, language, presentation, and graphic. The standard of assessment-instrument used in this study was in line with the standard of assessment-instrument of knowledge-enrichment book by Pusat Kurikulum dan Perbukuan (Puskurbuk) of Indonesian Ministry of Education and Culture. Written in communicative language, interactive pictures, and simplistic explanation about factual information of coal, the book acquired 92% of material-standard, 89.3% of activity-standard, and 83,3% graphic-standard with the â€œvery goodâ€ intepretation, while 80.5% for media-standard with the â€œgoodâ€ intepretation. Based on the efficacy-standard testing, the book had 0.35 gain-score, indicated that it can enhance studentsâ€™ knowledge in the â€˜middleâ€™ category. The result strengthened that the knowledge-enrichment book â€œKajian Fisis Batubaraâ€ was appropriate as a standardized and well-intepreted book. Keywords :Knowledge-enrichment book, Energy sources, Coal.